Transaksi Pihak Terkait atas Biaya Audit: Peran Efektivitas Komite Audit - Kristiyani, Dian (E-Jurnal Akuntansi; Vol 30 No 10 (2020), 2020)
The purpose of this study is to analyze the effect of related party transaction and the effectiveness of audit committee on audit fee. This research uses samples a  manufacturing company in Indonesia Stock Exchange (IDX) in 2014-2018. The sampling technique used purposive sampling. The total number of companies used as research samples is 118 companies. Using tools SPSS 20 and testing hypothesis using linear regression. The F test indicates a stable and significant model. R square is 58,7 percent. The results show that related party transactions have a significant positive effect and the effectiveness of the audit committee has a significant negative effect on audit fees. Keywords: Related Party Transaction; Effectiveness Of Audit Committee; Audit Fee.